Bone cement penetration pattern and primary stability testing in keeled and pegged glenoid components - Raiss, Patric; Pape, Guido; Kleinschmidt, Kerstin; Jäger, Sebastian; Sowa, Boris; Jakubowitz, Eike; Loew, Markus; Bruckner, Thomas; Rickert, Markus (Journal of shoulder and elbow surgery, 2011)
Background - It has been proposed that bone mineral density has an influence on cement penetration in hip and knee arthroplasty. The hypotheses of this study were that: 1) there is a negative correlation between bone mineral density (BMD) and cement penetration in cemented glenoid components; and 2) that implant design has an influence on cement penetration into the glenoid bone. - Methods - BMD of 10 pairs of fresh frozen scapulas was measured. Micro-computed tomography (micro-CT) scans in 3 different sections were analyzed after implantation of keeled and pegged glenoid components using a 3rd-generation cementing technique with a vacuum mixing system. Cement penetration was analyzed and correlated with BMD. Pull-out strength testing was performed to analyze primary stability. - Results - The overall peak BMD was 0.6 [g/cm2] (range, 0.33-0.98). A strong negative correlation between BMD and mean cement penetration was found for the peg (R2 = −.83; P < .003) and for the keel group (R2 = −.81; P < .005). Mean cement penetration was 78.4 mm2 (range, 60.6-94.2) in the keel and 113.9 mm2 (range, 78.2-143.4) in the peg group (P < .0001). In all cases, the components were pulled out of the cement mantle, whereas the bone-cement interfaces remained intact. The mean pull-out strength was 1093N (764-1343N) for keeled and 884N (650-1264N) for pegged components (P < .05). - Conclusion - A modern cementing technique, leading to a deep bonding between bone and cement, is crucial to prevent loosening of glenoid components. The findings of this study might help us to better understand the results of follow-up studies of cemented glenoid implants. Our results could be helpful for the choice of implants in patients with poor bone quality like osteoporosis or rheumatoid arthritis.